Bone health during endocrine therapy for cancer. Issue 11 (November 2018) - Rachner, Tilman D; Coleman, Robert; Hadji, Peyman; Hofbauer, Lorenz C
Summary: Preservation of bone health remains a long-term clinical challenge in patients with breast and prostate cancer. Osteoporosis, defined by a loss of bone mass and microarchitecture, often results in fragility fractures that are typically associated with a high socioeconomic burden. Endocrine therapy, a mainstay treatment in the management of patients with hormone-sensitive breast and prostate cancer in the adjuvant setting, commonly exerts adverse effects on the musculoskeletal system and is associated with an increased risk of osteoporosis and fractures. Adjuvant use of gonadotropin-releasing hormone analogues, which can also be used in metastatic disease, in combination with tamoxifen in premenopausal women, and aromatase inhibitors in postmenopausal women with hormone-sensitive breast cancer, causes rapid bone loss and fragility fractures. By contrast, selective oestrogen receptor modulators, such as tamoxifen, have bone-protective effects in postmenopausal women. In men with castration-sensitive prostate cancer, androgen deprivation is achieved with drugs that lower gonadotropin levels, and these drugs can be combined with androgen receptor antagonists. These therapies induce a high bone turnover with rapid bone loss that is reminiscent of the changes occurring in early menopause and result in an increased risk of fracture. In this Review, we describe how adjuvant endocrine therapies of breast and prostate cancer impair bone health and outline evidence from randomised controlled trials of strategies to reduce risk of fracture.